Islamic Music and Local Identity of Sundanese Ethnicity - Tohari, Amin (UIN Maulana Malik Ibrahim Malang, 2024)
Derived from the dimension of locality, terebang merges Sundanese ethnic and Islamic elements into a distinctive music genre. This article explores the forms of the Sundanese Islamic musical genre and how this genre is utilized at Islamic ritual events and on the urban stage. With the involvement of cultural activists supporting the Candralijaya band, this research also examines the challenges and criticisms from various groups concerning the integration of ethnicity and Islam. Based on an ethnographic expedition in Tasikmalaya, West Java, the findings reveal a unique significance in this genre that is not evident in other parts of Indonesia or the Muslim world, such as in the Middle East and Pakistan. This study highlights the importance of expressing 'Sundanese-Islamic feelings' through musical performance art. It argues that this music genre embodies a vernacular meaning born from two distinct origins, yet it has created a distinctive genre. This confirms that both sources maintain specific boundaries, each with its own unique 'flavors.' Future studies could explore how these musical performances can foster intercultural dialogue and understanding in diverse societies, potentially serving as a bridge between different religious and ethnic communities. Berawal dari dimensi lokalitas, terebang menggabungkan elemen-etnik Sunda dan Islam menjadi genre musik yang khas. Artikel ini mengeksplorasi bentuk-bentuk genre musik Islam Sunda dan bagaimana genre ini digunakan dalam acara ritual Islam dan di panggung urban. Dengan keterlibatan aktivis budaya yang mendukung band Candralijaya, penelitian ini juga mengkaji tantangan dan kritik dari berbagai kelompok mengenai integrasi etnisitas dan Islam. Berdasarkan ekspedisi etnografi di Tasikmalaya, Jawa Barat, temuan ini mengungkapkan sebuah keunikan dalam genre ini yang tidak terlihat di bagian lain Indonesia atau dunia Muslim, seperti di Timur Tengah dan Pakistan. Studi ini menyoroti pentingnya mengekspresikan 'perasaan Islam-Sunda' melalui seni pertunjukan musikal. Argumennya adalah bahwa genre musik ini mengandung makna vernakular yang berasal dari dua sumber berbeda, namun telah menciptakan genre yang berbeda. Ini membenarkan bahwa kedua sumber tersebut mempertahankan batas-batas tertentu, masing-masing dengan 'rasa' uniknya sendiri. Studi mendatang dapat mengeksplorasi bagaimana pertunjukan musik ini dapat mendorong dialog dan pemahaman lintas budaya dalam masyarakat yang beragam, berpotensi menjadi jembatan antara komunitas agama dan etnik yang berbeda.